PENGEMBANGAN VIDEO PEMBELAJARAN KIMIA SMA/MA MENGGUNAKAN CAMTASIA STUDIO 8 - Rizky Ariaji; Nasirsah Nasirsah; Salih Angraini Siregar (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2020)
One of the problems for chemical learning is that it is still the low development of teaching materials in the school so that students ' learning is still focused on teaching books provided by the schools. In this additional teaching materials in the form of instructional videos can affect students' learning will, so that students get a lot of information in the implementation of the learning process with the developed teaching materials by utilizing the source Existing natural resources around the students. The purpose of this research is to know the feasibility test of chemistry learning video using Camtasia Studio 8 and to know the opinion of teachers and lecturers of chemistry learning video using Camtasia Studio 8 on Class X odd semester developed in accordance with the BSNP standards. Research and Development (R&D) methods using 4-D Thiagarajan models include (define, design, develope, and disseminate). The research results for the average value of all aspects of eligibility standards based on the BSNP is 4.17 validity criteria of Valid and no need for revision.